Educated Women: Shaping Social Identity during the National Movement - Setyaningsih, Wahyu (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2022)
Abstract: Women's label as konco wingking, the second sex, demonstrates an intensely patriarchal culture. The national movement period was involved in realizing their independence. This article explains the role of educated women during the national movement. This study is historical research with a political and psychological approach to comprehend how educated women could gain hegemony and power to create their social identity both in the domestic and public spheres. This study found that during the national movement, the social identity of educated women was gaining an existence as subjects who carried out various roles and got equal rights with men, both in the domestic and public spheres. Being educated subjects, women are aware of their identity as independent individuals, human rights that should be respected, and an equal position with men.Abstrak: Label perempuan sebagai konco wingking, jenis kelamin kedua, menunjukkan budaya patriarki yang kental. Masa pergerakan nasional terlibat dalam mewujudkan kemerdekaannya. Artikel ini menjelaskan peran perempuan terpelajar selama pergerakan nasional. Kajian ini merupakan penelitian sejarah dengan pendekatan politik dan psikologis untuk memahami bagaimana perempuan terpelajar dapat memperoleh hegemoni dan kekuasaan untuk menciptakan identitas sosialnya baik di ranah domestik maupun publik. Kajian ini menemukan bahwa pada masa pergerakan nasional, identitas sosial perempuan terpelajar memperoleh eksistensi sebagai subjek yang menjalankan berbagai peran dan mendapat hak yang sama dengan laki-laki, baik di ranah domestik maupun publik. Sebagai subjek terpelajar, perempuan menyadari identitasnya sebagai individu yang mandiri, hak asasi manusia yang harus dihormati, dan kedudukan yang setara dengan laki-laki.